Chemical reactivity and binding interactions in ribonucleic acid‐peptide complexes. Issue 3 (17th November 2021) - Srivastava, Ruby
Abstract: The covalent and noncovalent backbone binding interactions in RNA‐peptide complexes were studied by DFT methods. Four RNA structures R1(GGCUAGCC), R2(AAUCGAUU), R3(GGGAUCCC), and R4(AAAGCUUU) has been selected for eight protonated peptides (DR, ER, GR, KR, NGR, RR, tmeGnd (tme), and VR) interactions based on an experimental study ( Anal Chem . 2019; 91:1659‐1664). Chemical reactivity theory is used to study the reactivity of eight peptides with global descriptors. Lower hardness values reflected low stability and high reactivity for the protonated peptides. DR, ER, GR, KR, NGR, RR, and VR show lower value of ω, μ while tme has high value of ω, μ . Larger highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) gap for ER, GR, and KR showed greater structural stability for peptides. AutoDock and PatchDock results indicated that R1, R2, and R4 retain hairpin structures while interacting with peptide complexes. The calculated binding energies of (R1–R4)‐peptide complexes from AutoDock tools are (1.49–11.12) kcal/mol. Results showed that the noncovalent interactions are stronger than the covalent interactions for R1‐peptide complexes. The reason might be the transfer of proton from protonated ligand to deprotonated RNA, which has initiated the loss of the ligand. Also it has been observed that proton transfer has become energetically unfavorable in presence of additional hydrogen bonds which is predicted in the experimental results.